A micologia na formação de professores : uma análise das licenciaturas em ciências biológicas no Estado de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This work was based on the observation, through personal experiences in Basic Education, of the difficulties of teachers in teaching and of students in understanding the subjects related to Mycology, as well as my anguish, shared by colleagues from the same area of formation, about the superficial form with which the fungi were approached in our graduations. In view of this, the research brought the following research problem: How is the content of Mycology being approached in the Bachelor's Degree in Biological Sciences? The dissertation was organized in chapters: in the first one were identified the Institutions of Higher Education that offer the Course of Biological Sciences, modality licenciatura, in the state of Goiás, their respective curricular matrices, menus of the disciplines that approach the content of Mycology and, the profile of the teachers who teach these subjects and how they are addressed. The results showed that fungi are approached in generalist disciplines, predominantly Microbiology or Botany, in which they occupy an insufficient working load, often being restricted to microfungi, or fungi of medical interest, sometimes with plants. Classes usually involve few practical activities, almost always occur exclusively in the laboratory and are restricted to micromycetes. The teacher responsible for the content usually has no specific training in Mycology. In the second chapter, the knowledge about the fungi among the graduating students of these courses was investigated. The results showed that these students have less knowledge than they should have, lacking in depth, with conceptual inaccuracies and presenting difficulties in developing critical and logical reasoning in formulating answers. Moreover, they showed an anthropocentric view, in which fungi are at the service of the human species, with little attention to their interactions and their ecological role. These fragilities hinder or even render unviable an efficient and quality-restricted scientific education in relation to scientific education. The last component of the dissertation consists of the presentation of the Educational Product, which was developed in function of the previous results and constitutes an educational blog as an updated and attractive support material to foster the teaching practice of both teacher trainers and teachers in formation , in the approach on fungi.
Mycology in teacher education : an analysis of undergraduate courses in Biological Sciences in the State of Goiás
Keywords: Fungos; Ensino Superior; Conhecimento micológico; Formação de Professores de Ciências; Formação de Professores de biologia; Matriz curricular; Fungi; Higher education; Mycological knowledge; Teacher Training in Science and Biology; Curriculum; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO